Assessment of Engagement and Managerial Skills in Terms of Placement in the Organization: An Empirical Study - Zuzana BIRKNEROVA; Anna TOMKOVA; Lucia ZBIHLEJOVA (Communications of International Proceedings, 2023)
The success and performance of the company depends largely on human resources, which form an unimaginable part of every successful company. Managers are in a position where they have direct impact and influence on employees. The world of business is dynamic; therefore, it is essential that the skills of managers are developed and thus they can ensure more effective management of people. The paper describes engagement and at the same time the possibilities of increasing the level of managerial skills. The aim of the research was to find out the existence of differences in the assessment of engagement and managerial skills from the point of view of placement in the organization. The research sample consisted of 312 respondents who assessed engagement by means of the ISA Engagement Scale questionnaire and the level of management skills using the AMC23 managerial competency assessment questionnaire. The obtained data were processed by the t-test for two independent samples in the statistical software IBM SPSS 26.
Keywords: managerial skills; engagement; managers; employees